Wisdom as an Outcome of Critical Thinking in the School Curriculum - Towndrow, Phillip A. (Beyond Words, 2015)
Abstract This article considers a way of enacting critical thinking in the school curriculum. An alternative to adopting a formal framework of critical thinking which may not be exhaustive or include desirable components, involves working towards the generation of wisdom—defined as the quality of having the experience, knowledge and insight to think and act aptly in a specific context for a particular purpose—as a way for learners to make meanings that potentially have personal and social significance. The article uses a real-world example to illustrate how critical thinking can be driven by inquiry and underpinned by explanation to demonstrate practical knowledge and understanding in specific circumstances. Keywords: wisdom, critical thinking, curriculum, instruction, task design, classroom practice